Cooperation on Stocks Recover - Filipe, José António (2013)
The study of cooperation shows that often it brings gains to the agents. In this study it is shown that cooperation is very interesting when exploiting marine live resources. Several kinds of models have been used to show the advantages of cooperation in fisheries (see Munro, 2002; Miller and Munro, 2002; Clark, 1980; or Levhari and Mirman, 1980, for example). In this study, a general model for fisheries is presented and a Cournot-Nash model supported on the variable fishing effort is introduced, both showing that cooperation is useful.